2020
DOI: 10.1007/s11694-020-00401-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of starch isolation process for sweet potato and characterization of the prepared starch

Abstract: The study was conducted to standardize the parameters of centrifugation method of starch isolation for sweet potato to yield better quality starch. The effects of solid-to-solvent ratio in slurry-making, numbers of blending, slurry filtration and starch washings were studied for obtaining maximum yield and purity of starch with desired color and amylose content. The goal of the study was to develop a suitable process for small scale/on-farm processing of sweet potato for preparation of starch. A widely grown p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 32 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…In general, the best tissue quality was observed in the samples packed with typical atmospheres, and the difference in this variable compared with the other treatments was significant ( p < .05; Table 1). Material firmness is an important aspect affecting the acceptability of fresh fruit to customers (Vithu et al., 2020). Degradation of the middle lamella of the cortical parenchyma cell wall, strength of the cell wall, cell to cell contact, and cellular turgor can affect the firmness of strawberries during storage.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the best tissue quality was observed in the samples packed with typical atmospheres, and the difference in this variable compared with the other treatments was significant ( p < .05; Table 1). Material firmness is an important aspect affecting the acceptability of fresh fruit to customers (Vithu et al., 2020). Degradation of the middle lamella of the cortical parenchyma cell wall, strength of the cell wall, cell to cell contact, and cellular turgor can affect the firmness of strawberries during storage.…”
Section: Resultsmentioning
confidence: 99%
“…Similar behaviors were observed in arracacha biofilms, where high whiteness values were obtained with 3-5% arracacha starch and 1% glycerol (Figure 1b). The similarities in the whiteness values of the biofilms may be attributed to the starch extraction process, [32,33] which may remove the pigment or other light-absorbing substances present in potato tubers and arracacha roots. [34][35][36] Whiteness values between 87 and 89.8 were previously obtained in biofilms made from 2-3% olluco starch.…”
Section: Optimization Of Variables Using Response Surface Methodologymentioning
confidence: 99%
“…The sweet potato starch was prepared according to the method described by Vithu et al [12] with some modification as shown in Fig. 1.…”
Section: Processing Of Sweet Potato Starch Powdermentioning
confidence: 99%